Pengaruh Disiplin Kerja terhadap Kinerja Pegawai Negeri Sipil pada Dinas Pendidikan Kota Jambi - Asmi Kurniawan (Science of Management and Students Research Journal (SMS), 2021)
The purpose of this study was to determine and describe the description of work discipline and employee performance at the Jambi City Education Office, as well as to determine and analyze the effect of work discipline on employee performance at the Jambi City Education Office. The analytical method used is quantitative data analysis method, namely the analysis used to test the relationship or influence of the independent variable (X) and the dependent variable (Y). The analytical tools in this study are simple linear regression analysis, hypothesis testing and the coefficient of determination (R2). Based on the criteria, the samples taken were 32 Civil Servants at the Jambi City Education Office. From the results 1. Discipline at the Jambi City Education Office is categorized as high with a score of 121 while performance is categorized as high with a score of 119.9. 2. Discipline variable (X) has a significance value of 0.000, where the P-value is smaller than 0.05 and the t-count is 5.580 which is greater than the t-table (2.042). This means that there is a significant influence between discipline (X) on the performance of civil servants (Y) at the Jambi City Education Office.